Soybean inoculation by spraying Bradyrhizobium over plants - Zilli, Jerri Édson; Marson, Leandro Carvalho; Marson, Bruno Franco; Gianluppi, Vicente; Campo, Rubens José; Hungria, Mariangela (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate a Bradyrhizobium inoculation method on soybean by spraying inoculant over plants. An experiment was conducted in the Cerrado of Roraima. Treatments tested were: control without inoculation; standard inoculation method with two doses of inoculant per hectare applied on seeds; inoculation with threefold standard inoculation dose applied 18 days after plants emergence (DAE); fertilization with 200 kg ha-1 of nitrogen, without inoculation. The inoculation by spraying on covering increased nodulation and plant dry matter in the 45 and 60 DAE. It also increased significantly grain yield and N content, similarly to N fertilization treatment, and was superior to the control, and inferior to the standard inoculation related to grain yield.